1994
DOI: 10.1021/ja00090a041
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of -Cl.cntdot..cntdot..cntdot.Cl- Intermolecular Interactions

Abstract: The controversy as to whether there is a specific attractive intermolecular force between chlorine atoms, of the charge-transfer or donor-acceptor type, is resolved using various analyses of experimental crystal structure data and theoretical calculations. The occurrence of Cl-Cl intermolecular contacts which are shorter than would be expected from the conventional isotropic van der Waals radius is shown to be most common in the crystal structures of fully or highly chlorinated hydrocarbons, and thus a consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
306
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(323 citation statements)
references
References 1 publication
8
306
0
3
Order By: Relevance
“…Such a conclusion was drawn after the analysis of interatomic distances in crystals. Later, in 1994, Price et al [33] were investigating the nature of R1-ClÁÁÁCl-R2 interactions; on the basis of the analysis of ClÁÁÁCl distances in crystals and also on the basis of quantum-chemical calculations they concluded that such interactions were stabilizing, but what is particularly important, for the first time the phenomenon of anisotropic charge distribution around halogen nuclei was directly linked with the phenomenon of the ClÁÁÁCl noncovalent bonding. (Note that due to the same mechanism of formation, the ClÁÁÁCl interaction can be considered as a specific type of X-bonding; however, the term ''dihalogen bond'' is also often used for such type of interactions to distinguish them from typical X-bonds (e.g., R-XÁÁÁN,O) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Such a conclusion was drawn after the analysis of interatomic distances in crystals. Later, in 1994, Price et al [33] were investigating the nature of R1-ClÁÁÁCl-R2 interactions; on the basis of the analysis of ClÁÁÁCl distances in crystals and also on the basis of quantum-chemical calculations they concluded that such interactions were stabilizing, but what is particularly important, for the first time the phenomenon of anisotropic charge distribution around halogen nuclei was directly linked with the phenomenon of the ClÁÁÁCl noncovalent bonding. (Note that due to the same mechanism of formation, the ClÁÁÁCl interaction can be considered as a specific type of X-bonding; however, the term ''dihalogen bond'' is also often used for such type of interactions to distinguish them from typical X-bonds (e.g., R-XÁÁÁN,O) [34].…”
Section: Introductionmentioning
confidence: 99%
“…32 The coadsorption model in this study is shown in Figure 3c. As a result of the coadsorption, weak solventsolute electrostatic interactions (CH arom £Cl) 33 function to stabilize the adsorbed structure in Type 2. Adsorption of the solvent molecules which occupy smaller surface area is estimated to be weaker than that of the pigment molecules.…”
Section: Resultsmentioning
confidence: 99%
“…These polarizations are referred to as -hole and gives origin to halogen bonds. [9][10][11][12] On the other hand, two oxygen atoms in carboxyl group have negative electrostatic potential. Thus, positive regions of bromine atoms are able to electrostatically interact with the negative part of the oxygen atoms in carboxyl groups of neighbouring molecules, indicating the halogen bonds formation of Br … O=C and Br … OH.…”
Section: Monolayers On Hopgmentioning
confidence: 99%
“…[9][10][11][12] Typical bonding energies of hydrogen bonds are from 1 to 167 kJ/mol depending on their environment, 15 while halogen bonds are from 6 to 180 kJ/mol. [9][10][11][12][13][14] Although typical halogen bonds are relatively weak compared with hydrogen bonds, it has shown that, in some cases, the strength of halogen bonds can surpass classical hydrogen bonds, resulting in halogen bonds being the dominant driving force in the three-dimensional crystallization of organic molecules and the association of biological molecules. 16,17 From this viewpoint, using halogen bonds for assembling 2D molecular structures has advanced in recent years.…”
Section: Introductionmentioning
confidence: 99%